Legionella monitoring in the New York City water distribution system 2017 to 2019. Issue 2 (9th March 2022) - Omoregie, Enoma; Szczerba, Adam; Novak, John; Rubinstein, Inessa; Chuang, Yayu; Wu, Jing; Wang, Jade; Kretz, Cecilia; Hughes, Scott; Capetanakis, Aspa; Freud, Salome; Rakeman, Jennifer L.
Abstract: This study investigated prevalence of Legionella in the New York City (NYC) water distribution system using International Organization for Standardization 11731:2017 and Legiolert (IDEXX, USA) culture‐based methods and polymerase chain reaction. All water samples met applicable Environmental Protection Agency and New York State water quality guidelines. Eighty‐five percent (448/528) of water samples were positive for Legionella DNA. Despite this, Legionella bacteria were detected in only 2.8% (15/544) of water samples using culture methods. All Legionella pneumophila culture‐positive samples were recovered from a single distribution site, which was undergoing a street reconstruction project. The site had conditions indicative of stagnation, and an adjacent building's service line was periodically backflowing. These factors indicate that L. pneumophila may have been introduced from an external source. The lack of culturable Legionella in samples with detectable Legionella DNA suggests that NYC practices are sufficient to protect against culturable Legionella in NYC's water distribution system.